Understanding the mode of action of AgroGain®, a biostimulant derived from the red seaweed Kappaphycus alvarezii in the stimulation of cotyledon expansion and growth of Cucumis sativa (cucumber) - Shukla, Pushp Sheel; Nivetha, Nagarajan; Nori, Sri Sailaja; Bose, Debayan; Kumar, Sawan; Khandelwal, Sachin; Critchley, Alan; Suryanarayan, Shrikumar (Frontiers in Plant Science, 2023)
Seaweed-based biostimulants are sustainable agriculture inputs that are known to have a multitude of beneficial effects on plant growth and productivity. This study demonstrates that Agrogain® (Product code: LBS6), a Kappaphycus alvarezii-derived biostimulant induced the expansion of cucumber cotyledons. Seven days treatment of LBS6-supplementation showed a 29.2% increase in area of expanded cotyledons, as compared to the control. LBS6-treated cotyledons also showed higher amylase activity, suggesting starch to sucrose conversion was used efficiently as an energy source during expansion. To understand the mechanisms of LBS6-induced expansion, real time gene expression analysis was carried out. This revealed that LBS6-treated cotyledons differentially modulated the expression of genes involved in cell division, cell number, cell expansion and cell size. LBS6 treatment also differentially regulated the expression of those genes involved in auxin and cytokinin metabolism. Further, foliar application of LBS6 on cucumber plants being grown under hydroponic conditions showed improved plant growth as compared to the control. The total leaf area of LBS6-sprayed plants increased by 19.1%, as compared to control. LBS6-sprayed plants efficiently regulated photosynthetic quenching by reducing loss via non-photochemical and non-regulatory quenching. LBS6 applications also modulated changes in the steady-state photosynthetic parameters of the cucumber leaves. It was demonstrated that LBS6 treatment modulated the electron and proton transport related pathways which help plants to efficiently utilize the photosynthetic radiation for optimal growth. These results provide clear evidence that bioactive compounds present in LBS6 improved the growth of cucumber plants by regulating the physiological as well as developmental pathways.